The Equation of Exchange Revisited - Dirk Kaiser (Kredit und Kapital, 2011)
The Equation of Exchange Revisited The article presents a more general version of the equation of exchange providing separately for a financial turnover of money as well as a corresponding financial velocity of money. This sheds a special theoretical light on the easy monetary policy implemented by the Federal Reserve between 2001 and 2004 and the enlargement of the financial sphere in the United States, which persisted until the recent financial crisis broke out – to become an international economic crisis in due course. (JEL E40, E52, G01, N12) – – Die Verkehrsgleichung wieder aufgenommen Eine allgemeinere Version der Verkehrsgleichung wird vorgestellt, die zusätzlich einen finanziellen Umsatz und eine finanzielle Umlaufgeschwindigkeit des Geldes vorsieht. Hierdurch erscheinen die leichte Geldpolitik der Federal Reserve in den Jahren 2001 bis 2004 und die Vergrößerung des Finanzsektors in den Vereinigten Staaten, die bis zum Ausbruch der jüngsten Finanzkrise und der sich anschließenden internationalen Wirtschaftskrise andauerte, in einem speziellen theoretischen Licht.
Keywords: E40; E52; G01; N12; 330